Assessment of the genotoxic effect of X-ray radiation on earthworms Lumbricus terrestris living in soils of Polesie radiation-ecological reserve - Kadukova, Alena; Veyalkina, Nataliya; Goncharov, Sergey; Cheshik, Ihor (Journal of the Belarusian State University. Ecology, 2024)
Earthworms are reference animal species for assessing the effects of radiation exposure on biota. The object of the study was earthworms of the species Lumbricus terrestris, it belongs to the soil group and live in the Polesie State Radiation-Ecological Reserve (PSRER) under conditions of chronic exposure to the radiation factor. The purpose of the work is to assess the level of damage to the genetic apparatus: the frequency of micronuclei and binucleate cells, as well as the spontaneous level and rate of repair of induced DNA damage after exposure to acute X-ray radiation at a dose of 4 Gy in coelomocytes of earthworms from populations inhabiting soils of areas with technogenically increased content of radionuclides. The calculated values of the absorbed dose rate from 137Cs for earthworms of the species L. terrestris living in the soil at the study sites in the PSRER 35 years after the Chernobyl accident, in almost all cases exceed the value of the most conservative existing safe level of radiation exposure on biota - 10 μGy/h, but do not reach the permissible radiation exposure level of 10 mGy/day established for earthworms in ICRP Publications 108. It was established that the spontaneous level of DNA damage (% DNA tail) in L. terrestris earthworms living in areas with different levels of radioactive contamination by 137Cs did not differ and amounted to 12.04 ± 1.32 (control area) and 14.36 ± 2.52 (PSRER), respectively. Exposure to acute X-ray radiation at a dose of 4 Gy led after 48 hours to an increase in the number of binucleate cells in coelomocyte populations; it was significantly higher in earthworms living in the soil of areas with increased levels of radionuclide contamination. The level of DNA damage in earthworms living in soils of areas with increased background radiation, 24 hours after exposure to acute X-ray irradiation at a dose of 4 Gy, decreased by 12.98% compared to the corresponding value after 0.1 hour, and in earthworms of the group comparison (Gomel region) - only by 5.88% compared to the corresponding value. The adaptive response in earthworms of the species L. terrestris have inhabited for a long time in the soils of the PSRER territories, manifested itself in the form of an increased rate of DNA repair and an increase in cell proliferation after acute X-ray irradiation at a dose of 4 Gy.